15x=23+6-8x

Simple and best practice solution for 15x=23+6-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15x=23+6-8x equation:



15x=23+6-8x
We move all terms to the left:
15x-(23+6-8x)=0
We add all the numbers together, and all the variables
15x-(-8x+29)=0
We get rid of parentheses
15x+8x-29=0
We add all the numbers together, and all the variables
23x-29=0
We move all terms containing x to the left, all other terms to the right
23x=29
x=29/23
x=1+6/23

See similar equations:

| 29=-1.5r+17 | | x-46=100 | | −8=x4+3-8=x4+3 | | 1=2(3x+4) | | .5c-25=-23 | | 2(3y+4)=3(3y-4)-7y | | 3c+-10=8 | | 0.05m+3.95=20 | | 107+x+(180-(11x-3))=180 | | (x+3)3=45 | | 6x+46=124 | | 0.2(20x+15)-9=-0.5(6x-8) | | 107-x+(180-(11x-3))=180 | | 7=3h-11 | | .2a+8=9 | | 1.55x=-2.55 | | x(4x+5)=130 | | 17x+4=18x-5 | | 7-14x=-7 | | x-15.5=17.5 | | 17a/3=-14 | | 2-6=y | | p+84=91 | | w-15=56 | | 6x+12=-5x+12 | | 24=12u | | M=300-10d | | 1/6(9t-8)=t+8/12 | | 6a+11+3a-2+2a=-3a-1+7a+31 | | 5x-18=(2x+12) | | 6(-2g-1)=-(13g+2)6(−2g−1)=−(13g+2 | | 8b+8-4b=b=5 |

Equations solver categories